2012
DOI: 10.1074/jbc.m112.424457
|View full text |Cite
|
Sign up to set email alerts
|

Staurosporines Disrupt Phosphatidylserine Trafficking and Mislocalize Ras Proteins

Abstract: Background: Ras proteins must be plasma membrane-localized for biological activity. Results: A high content screen identified staurosporines as inhibitors of Ras plasma membrane localization and K-Ras signal transmission by disrupting endosomal recycling of phosphatidylserine. Conclusion: Staurosporines are novel inhibitors of phosphatidylserine trafficking. Significance: Ras trafficking pathways and Ras spatiotemporal organization on the plasma membrane are valid targets for anti-Ras drug development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
143
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(151 citation statements)
references
References 50 publications
8
143
0
Order By: Relevance
“…An L(r)-r value above the 99% confidence interval demonstrates a nonrandom clustered distribution. Consistent with previous results, in wildtype (WT) cells we observed a nonrandom, clustered distribution of PS (Fairn et al, 2011;Cho et al, 2012; van der Hoeven Figure 2. Caveolin is essential for the regulation of K-Ras nanoclustering on the PM.…”
Section: Ras Nanoclusterssupporting
confidence: 80%
See 2 more Smart Citations
“…An L(r)-r value above the 99% confidence interval demonstrates a nonrandom clustered distribution. Consistent with previous results, in wildtype (WT) cells we observed a nonrandom, clustered distribution of PS (Fairn et al, 2011;Cho et al, 2012; van der Hoeven Figure 2. Caveolin is essential for the regulation of K-Ras nanoclustering on the PM.…”
Section: Ras Nanoclusterssupporting
confidence: 80%
“…In consequence, H-and K-Ras assemble into spatially nonoverlapping nanoclusters with further lateral segregation into nonoverlapping GDP and GTP nanoclusters (Prior et al, 2003a;Plowman et al, 2005Plowman et al, , 2008Roy et al, 2005;Zhou et al, 2012). H-Ras associates with cholesterol-dependent nanoclusters on the inner leaflet of the PM when in an inactive GDP-bound state and, upon GTP loading, switches to cholesterol-insensitive nanodomains; K-Ras occupies cholesterol-insensitive nanoclusters in both GTP-and GDP-bound states that have been closely linked with phosphatidylserine (PS; Cho et al, 2012;van der Hoeven et al, 2013). Ras.GTP nanoclusters are the sole sites of effector recruitment and activation on the PM (Hibino et al, 2003;Murakoshi et al, 2004;Tian et al, 2007;Plowman et al, 2008), such that Ras signal transmission is abrogated if MEFs (n = 6).…”
Section: Cav1 Deficiency Is Associated With Changes In Membrane Lipidmentioning
confidence: 99%
See 1 more Smart Citation
“…Treating MDCK cells with staurosporine (STS) at low sub-apoptotic concentrations causes the relocalization of PtdSer from the plasma membrane to endosomes through an uncharacterized mechanism (Cho et al, 2012). Consistent with this finding, we found that treatment of CHO cells with STS led to the relocalization of the PtdSer biosensor GFP-Lact-C2 to endosomal compartments.…”
Section: Acute Alterations In Ptdser Distribution Alter Cholesterol Dsupporting
confidence: 77%
“…Attempts to abrogate the plasma membrane binding of Ras, which is required for biological activity, by inhibiting farnesyl transferase (6,7) have failed because N-Ras and K-Ras are also good substrates for geranylgeranyl transferase 1 in cells treated with farnesyl transferase inhibitors (8,9). Other efforts along this line include the development of farnesyl analogs, currently in clinical trials (10), and other compounds that dislodge Ras from the plasma membrane (11,12). Although the potential therapeutic value and mechanism of action of these compounds are still under investigation, it is clear that they do not directly bind to Ras.…”
mentioning
confidence: 99%